Using Zoom Meeting as Learning Medium on Speaking Online Class - Kadnawi (LPPM IAI Hasanuddin Pare-Kediri, 2022)
This study was conducted to the problem of using Zoom Meeting as learning medium. This research used descriptive qualitative research design. The population of this research was student of DELTA Education Center. The sample of this research was the student of Speaking Online Class. The research instrument was interview and documentation. The result of the analysis showed Learning English through 1) E-Learning during the Covid-19 pandemic; some of them stated that learning English while at home is quite good even it needs more time to do online. 2) The lesson which is given by PPT, so the students need to prepare it first. They used to study with book, due to pandemic, so they use PPT for their handbook in learning activity. 3) The students need more time to get signal. Because every place has own signal fo having the class. Sometimes they get sufficient signal, suddenly they lose the signal. In the contrary, they lose the signal, but for several minutes they get the signal. 4) The students are from house wives, so they need specific time to study English. It is about 4-5 p.m. every day. 5) The students need to create email, because the learning activity is online. Might as well, they must create email account. 6) To join zoom meeting needs an hour to log in, because they need to connect the signal and waiting from the host.